KEMITRAAN ANTARA SEKOLAH, ORANG TUA, DAN LEMBAGA-LEMBAGA SOSIAL KEMASYARAKATAN DI MADRASAH ALIYAH NEGERI SALATIGA - Fatchurrohman Fatchurrohman (Akademika : Jurnal Pemikiran Islam, 2018)
Abstract This study was aimed at determining the background of thought that underlies the education partnership in MAN Salatiga, the implementation of educational partnerships among the schools, parents, and social institutions in MAN Salatiga, and the impact of the partnerships among the schools, parents, and social institutions in the city Salatiga to improve the quality of schools, school culture, graduates, and parents. This type of research was a qualitative interpretive approach, which took place in MAN Salatiga, and community social institutions (Indonesian Red Cross, Indonesian National Sports Committee, Asmoro Budoyo Circle of Friends, Prana Shakti Jaka Tingkir Respiratory Self Defense College) in the city of Salatiga. Data were collected through interviews, observation, and document study. The data were then analyzed by following the stages developed by Yin and Stake, namely the stage of holistic analysis, embedded analysis, analysis of themes, within case analysis, and cross case analysis. The results of the study show that MAN Salatiga sees the need to utilize various resources in the community to overcome various limitations in the implementation of education in order to meet the demands of the community. The development of educational partnerships in MAN Salatiga is supported by social capital which is influenced by the type of school, initiative and interest, parental circumstances, school policy and political participation. Education partnerships in MAN Salatiga affect the quality of the schools, graduates, and parents. Keywords: Partnership, School, and Community Social Institutions Abstrak Penelitian ini bertujuan untuk mengetahui latar belakang pemikiran yang mendasari kemitraan pendidikan di MAN Salatiga, pelaksanaan kemitraan pendidikan antara sekolah, orang tua, dan institusi sosial kemasyarakatan di MAN Salatiga, dan dampak kemitraan antara sekolah, orang tua, dan lembaga-lembaga sosial kemasyarakatan di kota Salatiga terhadap perbaikan kualitas sekolah, budaya sekolah, lulusannya, dan orang tua. Jenis penelitian ini adalah kualitatif dengan pendekatan interpretatif, yang mengambil lokasi di MAN Salatiga, dan lembaga sosial kemasyarakatan (Palang Merah Indonesia, Komite Olahraga Nasional Indonesia, Paguyuban Asmoro Budoyo, Perguruan Beladiri Pernafasan Prana Shakti Jaka Tingkir) di kota Salatiga. Pengambilan data dilakukan melalui wawancara, observasi, dan studi dokumen. Data yang terkumpul dianalisis dengan mengikuti tahapan yang dikembangkan oleh Yin and Stake, yaitu tahap holistic analysis, embedded analysis, analysis of theme, within case analysis, dan cross case analysis. Berdasarkan pembahasan dapat disimpulkan, bahwa MAN Salatiga memandang perlunya meman-faatkan berbagai sumber daya dalam masyarakat untuk mengatasi berbagai keterbatasan penyelenggaraan pendidikan dalam rangka memenuhi tuntutan kebutuhan masyarakat. Pengembangan kemitraan pendidikan di MAN Salatiga didukung oleh modal sosial yang dipengaruhi oleh jenis sekolah, inisiatif dan interest, keadaan orang tua, kebijakan sekolah dan partisipasi politik. Kemitraan pendidikan di MAN Salatiga mempengaruhi mutu sekolah, lulusan, dan orang tua. Kata Kunci : Kemitraan, Sekolah, dan Lembaga Sosial Kemasyarakatan